(untitled) (Comprehensive Journal of Science, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia that leads to serious vascular and systemic complications. The red cell distribution width (RDW), a routinely measured hematological index reflecting erythrocyte size variability, has recently been proposed as a potential biomarker for metabolic and inflammatory disorders, including diabetes. This case–control study aimed to evaluate the diagnostic significance of RDW among diabetic and non-diabetic individuals in Tarhuna City, Libya. A total of 160 participants (80 diabetics and 80 non-diabetics) were enrolled, and their demographic, biochemical, and hematological data—including fasting blood glucose (FBS), glycated hemoglobin (HbA1c), and RDW indices (RDW-SD and RDW-CV)—were analyzed using SPSS version 23. While diabetic patients exhibited significantly higher mean values of FBS, HbA1c, triglycerides, and platelet counts (p < 0.05), no significant differences were observed in RDW-SD (41.78 ± 3.78 vs. 41.72 ± 4.06, p = 0.915) or RDW-CV (13.52 ± 1.80 vs. 14.11 ± 2.68, p = 0.108) between diabetic and non-diabetic groups. Correlation and regression analyses revealed no significant association between RDW and glycemic parameters, and receiver operating characteristic (ROC) curve analysis demonstrated limited diagnostic performance (AUC = 0.509 for RDW-SD and 0.576 for RDW-CV). These findings indicate that RDW is not significantly associated with diabetes mellitus and lacks sufficient sensitivity or specificity as a diagnostic biomarker. Larger, multi-centered studies incorporating additional inflammatory and metabolic indicators are warranted to further explore the potential role of RDW in diabetes risk assessment and disease monitoring.